Short Communication: Molecular characteristic of taro white cattle based on DNA microsatellite markers - LUH GEDE SRI SURYA HERYANI; I NENGAH WANDIA; I WAYAN SUARNA; I KETUT PUJA; NI NYOMAN WERDI SUSARI; KADEK KARANG AGUSTINA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Heryani LGSS, Wandia IN, Suarna IW, Puja IK, Susari NNW, Agustina KK. 2019. Short Communication: Molecular characteristic of taro white cattle based on DNA microsatellite markers. Biodiversitas 20: 671-675. This research was conducted to assess and characterize the genetics of Taro White cattle. Genetic characterizations of this cattle are essential to conservation and breeding program. A total of 18 samples and 4 pairs of microsatellite DNA markers (BM2113, BM1824, INRA023, and ETH225) were amplified by PCR and the products were run on 8% bis-Acrylamide gels. All microsatellite markers were successfully amplified with a mean allelic number of 3.25. Means of observed and expected heterozygosity were found to be 0,25 and 0,628. The Polymorphism Information Content (PIC) values ranged from 0.448 (BM1824) to 0.627 (BM2113) and fixation index were 0.620. The deviation from Hardy-Weinberg equilibrium revealed that Taro White cattle population exhibited significant deviations from Hardy-Weinberg equilibrium (HWE) and possessed a possibility of inbreeding. The microsatellite loci used or focused in the present study further validate their use for evaluation of genetic diversity of Taro White